The first records of Polygala westii (Polygalaceae) for South Africa (North-West Province) and a key to the southern African Polygala species in the Section Tetrasepalae - Bester, Stoffel Petrus; Paiva, Jorge (Phytotaxa, 2015)
The first record of Polygala westii (Polygalaceae) from the North-West Province (South Africa) is reported on here. The species is very rare and has previously only been collected in two separate gatherings. This species is characterised by having bracts and bracteoles caducous, the anterior sepals connate at least as much as half of their length and seeds pubescent and carunculate. It grows in a habitat that are severely impacted by agriculture and mining. A preliminary assessment of its conservation status is given. A key to the South African species in the subsection (Tetrasepalae) to which P. westii belong is provided. The aim of this paper is to highlight the species in order to stimulate the lookout for more material of this species.